Новый вид жужелиц рода Carterus (Coleoptera, Carabidae) - Замотайлов, А.С. (Вестник зоологии, 1988)
Описываемый ниже вид обнаружен при обработке сборов последних лет с Северо-Западного Кавказа и разборе материалов Зоологического института АН СССР (ЗИН) и Зоологического музея МГУ (ЗММ). Голотип нового вида хранится в ЗИН, паратипы — там же, в ЗММ и Институте зоологии им. И. И. Шмальгаузена АН УССР. C. (C) lutshniki sp. n. is described from Krasnodarsky Krai (holotype), Stavropolsky Krai and the Crimea. Type material is deposited in Zoological Institute, USSR Academy of Sciences, Leningrad (including holotype), Zoological Museum of the Moscow University and in the Institute of Zoology, Ukrainian SSR Academy of Sciences, Kiev.